Numerical simulation of impinging jet flows by modified MPS method. Issue 4 (15th June 2015) - Y.T. Feng, Professor Xikui Li, Professor Yuangqiang Tan; Professor Shunying Ji, Professor; Tang, Zhenyuan; Wan, Decheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The jet impingement usually accompanying large interface movement is studied by the in-house solver MLParticle-SJTU based on the modified moving particle semi-implicit (MPS) method, which can provide more accurate pressure fields and deformed interface shape. The comparisons of the pressure distribution and the shape of free surface between the presented numerical results and the analytical solution are investigated. The paper aims to discuss these issues. Design/methodology/approach – To avoid the instability in traditional MPS, a modified MPS method is employed, which include mixed source term for Poisson pressure equation (PPE), kernel function without singularity, momentum conservative gradient model and highly precise free surface detection approach. Detailed analysis on improved schemes in the modified MPS is carried out. In particular, three kinds of source term in PPE are considered, including: particle number density (PND) method, mixed source term method and divergence-free method. Two typical kernel functions containing original kernel function with singularity and modified kernel function without singularity are analyzed. Three kinds of pressure gradient are considered: original pressure gradient (OPG), conservative pressure gradient (CPG) and modified pressure gradient (MPG). In addition, particle convergence is performed by running the simulation with various spatial resolutions. Finally, the comparison of the pressure fields by the modified MPS and by SPH is presented. Findings – The modified MPS method can provide a reliable pressure distribution and the shape of the free surface compared to the analytical solution in a steady state after the water jet impinging on the wall. Specifically, mixed source term in PPE can give a reasonable profile of the shape of free surface and pressure distribution, while PND method adopted in the traditional MPS is not stable in simulation, and divergence-free method cannot produce rational pressure field near the wall. Two kernel functions show similar pressure field, however, the kernel function without singularity is preferred in this case to predict the profile of free surface and pressure on the wall. The shape of free surface by CPG and MPG is agreement with the analytical solution, while a great discrepancy can be observed by OPG. The pressure peak by MPG is closer to the analytical solution than that by CPG, while the pressure distribution on the right hand side of the pressure peak by latter is better match with the analytical solution than that by former. Besides, fine spatial resolution is necessary to achieve a good agreement with analytical results. In addition, the pressure field by the modified MPS is also quite similar to that by SPH, and this can further validate the reliable of current modified MPS. Originality/value – The present modified MPS appears to be a stable and reliable tool to deal with the impinging jet flow problems involving large interface movement. Mixed source term in PPE is superior to PND adopted in the traditional MPS and divergence-free method. The kernel function without singularity is preferred to improve the computational accuracy in this case. CPG is a good choice to obtain the shape of free surface and the pressure distribution by jet impingement.